MicroRNA Let-7f-5p Promotes Bone Marrow Mesenchymal Stem Cells Survival by Targeting Caspase-3 in Alzheimer Disease Model - Han, Linlin; Zhou, Yan; Zhang, Ruiyi; Wu, Kaimin; Lu, Yanhui; Li, Yanfei; Duan, Ranran; Yao, Yaobing; Zhu, Dengna; Jia, Yanjie (Frontiers in Neuroscience, 2018)
Widespread death of transplanted mesenchymal stem cells (MSCs) hampers the development of stem cell therapy for Alzheimer disease (AD). Cell pre-conditioning might help cope with this challenge. We tested whether let-7f-5p-modified MSCs could prolong the survival of MSCs after transplantation. When exposed to Aβ25-35 in vitro, MSCs showed significant early apoptosis with decrease in the let-7f-5p levels and increased caspase-3 expression. Upregulating microRNA let-7f-5p in MSCs alleviated Aβ25-35-induced apoptosis by decreasing the caspase-3 levels. After computerized analysis and the luciferase reporter assay, we identified that caspases-3 was the target gene of let-7f-5p. In vivo, hematoxylin and eosin staining confirmed the success of MSCs transplantation into the lateral ventricles, and the let-7f-5p upregulation group showed the lowest apoptotic rate of MSCs detected by TUNEL immunohistochemistry analysis and immunofluorescence. Similarly, bioluminescent imaging showed that let-7f-5p upregulation moderately prolonged the retention of MSCs in brain. In summary, we identified the anti-apoptotic role of let-7f-5p in Aβ25-35-induced cytotoxicity, as well as the protective effect of let-7f-5p on survival of grafted MSCs by targeting caspase-3 in AD models. These findings show a promising approach of microRNA-modified MSCs transplantation as a therapy for neurodegenerative diseases.